Revealing Gender Resistance In Contemporary Painting: The Perspective Of Female Artists In Yogyakarta - R. Angga Bagus Kusnanto; Tri Marhaeni Pudji Astuti; Djuli Djati Prambudi; Syakir (Lembaga Bale Literasi, 2025)
Contemporary art in Yogyakarta has developed into a medium of expression that not only reflects visual aesthetics but also voices criticism of gender inequality. Female artists such as Lucia Hartini and Diah Yulianti use art as a tool to challenge social constructs that limit gender roles and expressions. This study aims to examine how the paintings of Lucia Hartini and Diah Yulianti can serve as a form of resistance against existing gender norms in society. This study uses a qualitative approach with a case study design, involving in-depth interviews and visual analysis of the artists' works. Data was collected through direct interviews and observation of relevant artworks to reveal themes that emerged in gender representation. The results show that both artists use art as a medium to challenge patriarchal norms and fight for gender equality. Their works depict resistance to gender stereotypes and representations of women's bodies that are more free and independent. This study shows that art can serve as a powerful tool for changing perceptions of gender and fighting for equality. These findings have important implications for understanding art as a medium for social change in the context of local culture.